2019
DOI: 10.1016/j.gie.2018.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative biopsy sampling on severe submucosal fibrosis on endoscopic submucosal dissection for colorectal laterally spreading tumors: a propensity score analysis

Abstract: Preoperative biopsy sampling for colorectal LSTs might cause severe submucosal fibrosis but has no adverse influence on clinical outcomes of ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
0
29
0
2
Order By: Relevance
“…Previous studies demonstrated that biopsy history and delayed ESD after initial biopsy were independent predictive factors for endoscopic submucosal fibrosis ( 12 , 15 ). To test the hypothesis that biopsy is closely related to a higher risk of endoscopic submucosal fibrosis and thus results in more complications of ESD, we first investigated the relationship between biopsy and ESD outcomes.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Previous studies demonstrated that biopsy history and delayed ESD after initial biopsy were independent predictive factors for endoscopic submucosal fibrosis ( 12 , 15 ). To test the hypothesis that biopsy is closely related to a higher risk of endoscopic submucosal fibrosis and thus results in more complications of ESD, we first investigated the relationship between biopsy and ESD outcomes.…”
Section: Resultsmentioning
confidence: 93%
“…As shown in Table 4 , to further validate whether the biopsy history is a predictor for submucosal fibrosis, as has been reported elsewhere ( 12 , 15 ), and investigate the other relevant clinicopathologic risk factors, we compared the nonsubmucosal (F0, n = 109) and submucosal fibrosis groups (F1/F2, n = 58). Univariate analysis demonstrated that the 2 groups did not differ significantly regarding average age, gender ratio, alcohol consumption, tumor location, circumferential extension, iodine staining history, and length of lesions (all P > 0.05), which suggested good comparability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations